Evaluation of urban ants (hymenoptera: formicidae) as vectors of microorganisms in residential and industrial environments: II. Fungi - De Zarzuela, Maria Fernanda M. [UNESP]; Campos-Farinha, Ana Eugênia de C. [UNESP]; Russomanno, Olga M. R. [UNESP]; Kruppa, Pedro C. [UNESP]; Gonçalez, Edlayne [UNESP] (My University, 2007)
Collections in households and industrial kitchens were done aiming at evaluating the potential of urban ants in spreading fungi. The most abundant ant species in households were Tapinoma melanocephalum and Paratrechina longicornis. In industrial kitchens Paratrechina longicornis and Monomorium floricola were the most common. Tapinoma melanocephalum was the species that most carried fungi, followed by Paratrechina longicornis, Tetramorium sp., Monomorium pharaonis and Monomorium floricola. An aflatoxigenic strain of Aspergillus flavus was isolated.
Keywords: Fungi; Mycotoxins; Urban ants; Vectors; Aspergillus flavus; Formicidae; Hymenoptera; Monomorium floricola; Monomorium pharaonis; Paratrechina longicornis; Tapinoma melanocephalum; Tetramorium